2018
DOI: 10.1039/c7em00375g
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure–activity relationships for primary aerobic biodegradation of organic chemicals in pristine surface waters: starting points for predicting biodegradation under acclimatization

Abstract: Microbial biomass and acclimation can affect the removal of organic chemicals in natural surface waters. In order to account for these effects and develop more robust models for biodegradation, we have compiled and curated removal data for un-acclimated (pristine) surface waters on which we developed quantitative structure-activity relationships (QSARs). Global analysis of the very heterogeneous dataset including neutral, anionic, cationic and zwitterionic chemicals (N = 233) using a random forest algorithm sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 96 publications
3
45
2
Order By: Relevance
“…In summary, we did not find any effect of concentration on pharmaceutical removal percentage under the conditions tested in our membrane bioreactor. These results are in contradiction to other studies reporting a correlation between influent concentration and removal percentage of some OMPs in WWTPs(Nolte et al, 2018;Onesios-Barry et al, 2014;Wang et al, 2020).Onesios-Barry et al reported a negative correlation between concentration and removal for pharmaceuticals such as fluorouracil in laboratory columns inoculated with wastewater effluent. The lower removal values at higher concentrations might be related to toxicity.…”
contrasting
confidence: 65%
See 3 more Smart Citations
“…In summary, we did not find any effect of concentration on pharmaceutical removal percentage under the conditions tested in our membrane bioreactor. These results are in contradiction to other studies reporting a correlation between influent concentration and removal percentage of some OMPs in WWTPs(Nolte et al, 2018;Onesios-Barry et al, 2014;Wang et al, 2020).Onesios-Barry et al reported a negative correlation between concentration and removal for pharmaceuticals such as fluorouracil in laboratory columns inoculated with wastewater effluent. The lower removal values at higher concentrations might be related to toxicity.…”
contrasting
confidence: 65%
“…diclofenac, metoprolol). The removal differences between compounds is partially governed by the chemical structure's properties (Nolte et al, 2020;Nolte et al, 2018). For example, charged compounds are less biodegradable than neutral compounds probably due to a cellular uptake limitation Nolte et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The execution of computational tools and bioinformatics resources is an advanced approach toward the pesticide bioremediation (Malla et al, 2018; Vanacek et al, 2018). It takes the online platform of biodegradative databases publicly accessed for retrieving information on biodegradation of xenobiotic (pesticide) by microorganisms and biodegradation pathways of persistent chemicals (Nolte et al, 2018). These databases comprise the University of Minnesota Biocatalysis/Biodegradation Database (UM-BBD), Biodegradation Network-Molecular Biology database (Bionemo), Pesticide Target interaction database (PTID), Microbial Genome Database (MBGD), Biodegradative Oxygenases Database (OxDBase), BioCyc and MetaCyc compatible with both windows as well as Linux operating systems (Arora and Bae, 2014).…”
Section: Keys Of Systems Biologymentioning
confidence: 99%